2022
DOI: 10.1101/2022.01.31.478480
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A subset of gut leukocytes have telomerase-dependent “hyper-long” telomeres and require telomerase for function in zebrafish

Abstract: Telomerase, the enzyme capable of elongating telomeres, is usually restricted in human somatic cells, which contributes to progressive telomere shortening with cell-division and ageing. Using the zebrafish model, we show that subsets gut immune cells have telomerase-dependent 'hyper-long' telomeres, which we identified as being predominantly macrophages and dendritics (mpeg1.1+ and cd45+mhcII+). Notably, mpeg1.1+ macrophages have much longer telomeres in the gut than in their haematopoietic tissue of origin, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 105 publications
(176 reference statements)
0
4
0
Order By: Relevance
“…Telomerase has been described to have both canonical (telomere elongation) and non-canonical (telomere elongation-independent) functions. We therefore set out to determine the key molecular changes occurring in gut mpeg + cells in the absence of telomerase (tert), at the young age of c.5 months, where the levels of critically short telomeres are not yet sufficient to induce a significant accumulation of DNA damage response markers [56,72]. This means that most changes that we detect in the gut of young tert −/− animals are more likely to be due to absence of tert itself and its noncanonical functions, rather than telomere-induced DNA damage.…”
Section: Telomerase Depletion Accelerates Age-associated Increased Ap...mentioning
confidence: 99%
See 1 more Smart Citation
“…Telomerase has been described to have both canonical (telomere elongation) and non-canonical (telomere elongation-independent) functions. We therefore set out to determine the key molecular changes occurring in gut mpeg + cells in the absence of telomerase (tert), at the young age of c.5 months, where the levels of critically short telomeres are not yet sufficient to induce a significant accumulation of DNA damage response markers [56,72]. This means that most changes that we detect in the gut of young tert −/− animals are more likely to be due to absence of tert itself and its noncanonical functions, rather than telomere-induced DNA damage.…”
Section: Telomerase Depletion Accelerates Age-associated Increased Ap...mentioning
confidence: 99%
“…Genotyping was performed by PCR of the tert gene [29,30]. The telomerase null mutant (tert −/− ) zebrafish, extensively characterised elsewhere [29][30][31]72], displays no telomerase activity and has significantly shorter telomeres from birth, ageing and dying prematurely [29]. While tert −/− fish have a lifespan of c.12-20 months, WT fish typically die between 36-42 months of age [29,30].…”
Section: Zebrafish Strains Ages and Sexmentioning
confidence: 99%
“…As recently showed in (Dambroise et al, 2016), zebrafish age following the two-phase model first proposed flies (Tricoire & Rera, 2015), based on the age-related intestinal permeability assessed using the Smurf assay they previously described (Rera, Clark, & Walker, 2012). Moreover, we have recently shown that gut permeability with ageing, in zebrafish, is accelerated in the absence of telomerase (tert -/-) (Pam S. Ellis, 2022).…”
Section: Main Hallmarks Of Ageingmentioning
confidence: 99%
“…As recently showed in (Dambroise et al, 2016), zebrafish age following the two-phase model first proposed flies (Tricoire & Rera, 2015), based on the age-related intestinal permeability assessed using the Smurf assay they previously described (Rera, Clark, & Walker, 2012). Moreover, we have recently shown that gut permeability with ageing is accelerated in the absence of telomerase (tert -/-) (Pam S. Ellis, 2022). Following this model and considering the longevity curve from the population we sampled, the proportion of Smurfs might have been approximately, <10% at 2 month, 25% at 9 month, 50% at 22 months and >80% at 35 months.…”
Section: Main Hallmarks Of Ageingmentioning
confidence: 99%